2016
DOI: 10.1016/j.bpj.2015.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Water States in Cryopreserved Cells Reveals Tolerance toward Ice Crystallization

Abstract: Complex living systems such as mammalian cells can be arrested in a solid phase by ultrarapid cooling. This allows for precise observation of cellular structures as well as cryopreservation of cells. The state of water, the main constituent of biological samples, is crucial for the success of cryogenic applications. Water exhibits many different solid states. If it is cooled extremely rapidly, liquid water turns into amorphous ice, also called vitreous water, a glassy and amorphous solid. For cryo-preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 50 publications
1
59
0
1
Order By: Relevance
“…Apart from the cooling rate, the warming rate also represents an important parameter Recent studies (16,30,31) have shown that recrystallization of vitreous water and crystal growth during the warming process can inflict lethal damage on the cells. The transient simulation of the heat transfer for the warming process was also performed (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the cooling rate, the warming rate also represents an important parameter Recent studies (16,30,31) have shown that recrystallization of vitreous water and crystal growth during the warming process can inflict lethal damage on the cells. The transient simulation of the heat transfer for the warming process was also performed (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These CCRs are experimentally unattainable values for droplets of a diameter >10 μm (as, e.g., in cells). Fortunately, complete vitrification is not necessary for cryopreservation, i.e., cells seem to tolerate well the presence of small ice crystals (less than 1 μm) (16). Since the tolerance depends on the CPAs, the tolerance in CPA-free cryopreservation can be expected to be very low.…”
mentioning
confidence: 99%
“…Therefore, by Fourier's law, the rate of warming through the critical zone of ice nucleation and formation will be slower than the rate of cooling through this zone [32]. Previously, it was presumed that CPAs exerted their main effects by preventing ice crystallization during cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Direct immersion in liquid nitrogen (LN), or flash-cooling, induces intracellular freezing earlier in the process, which prevents rapid cell dehydration. Furthermore, the ice crystals that form within the cell are minuscule and do not cause any damage (Engelmann & Dussert, 2013;Huebinger et al, 2016). As such, the EA with high water concentration that are flash-cooled could survive cryopreservation (Normah & Makeen, 2008;Berjak & Pammenter, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At this temperature, water molecules form "ice embryos" that are of a critical size and thermodynamically capable of growing and forming into crystals (Thomson et al, 2015;Lo et al, 2017). Ice crystals affect the structural and osmotic integrity of cells causing physical ruptures and mechanical damage (Pammenter & Berjak, 2014;Huebinger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%